Crystalline and amorphous PEO based ceramic coatings on AA6061: Nanoindentation and corrosion studies. Issue 10 (15th May 2021) - Pillai, Anju M.; Ghosh, Rahul; Dey, Arjun; Prajwal, K.; Rajendra, A.; Sharma, A.K.; Sampath, S.
Abstract: Present study reports the detailed nanomechanical and corrosion behaviours of crystalline and amorphous plasma electrolytic oxidation (PEO) coatings developed on Aluminium alloy-6061. The concentration of sodium silicate in the electrolyte is tailored to achieve crystalline and amorphous natures of the PEO coatings. X-ray diffraction (XRD), scanning electron microscopy (SEM) and nanoprofilometry techniques are utilized to investigate microstructural and morphological properties of the PEO coatings. XRD studies confirmed that crystalline ceramic phases are obtained at lower silicate concentration while amorphous nature occurred for comparatively higher concentration of silicate in the electrolyte. Nanoindentation technique is utilized to study the mechanical properties such as hardness (H) and Young's modulus (E) of the PEO coatings. The scatter of the data is treated with well-established Weibull statistical method. Finally, in depth corrosion behaviour of the coatings are investigated by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization techniques. Amorphous coatings exhibited superior mechanical properties compared to the crystalline coatings. This is possibly linked with the presence of aluminosilicate phases and difference in silicon content in the coatings. However, as expected crystalline PEO coatings offer better corrosion resistance than the amorphous coatings and this behaviour is explained in terms of porosity contents of the coatings.